Pengaruh Brand Image, Brand Love dan Brand Experience terhadap Brand Loyalty dengan Mediasi Brand Trust pada Kedai Mixue di Kota Surabaya - Michelle Angelina; Lena Ellitan; Yuliasti Ika Handayani (CV. Ulil Albab Corp, 2023)
This research objective is to analyze the effect of Brand image, Brand love, and Brand experience on Brand loyalty with the Mediation of Brand trust at Mixue Shops in Surabaya City. On these research, researcher sampling technique used is non-probability sampling by purposive sampling. The sample used in this study amounted to 140 respondents. Requirements for respondents in this study are at least 17 years old, lived in Surabaya, and buy at least 3 times per month. The data analysis technique used is SEM-PLS analysis with the SmartPLS 4 program. The result of the research are prove that brand image and brand love have a significant influence on brand trust. Meanwhile, brand experience doesn’t have significant effect on brand trust, and brand trust has significant positive effect on brand loyalty. Practical implication from the research for Mixue is to give better services so, it will increase cunsomer loyalty to Mixue in Surabaya city.